1351. A Retrospective Database Study of Lyme Borreliosis Incidence and Distribution in Poland from 2015 to 2019. (15th December 2022) - Paradowska-Stankiewicz, Iwona Iwona; Zbrzeźniak, Jakub; Skufca, Jozica; Nagarajan, Archana; Ochocka, Paulina; Pilz, Andreas; Vyse, Andrew; Begier, Elizabeth; Dzingina, Mendwas; Blum, Maxim; Riera, Margarita; Gessner, Bradford; et al.
Abstract: Background: Lyme borreliosis (LB), a tick-borne disease caused by Borrelia burgdorferi sensu lato, has been subject to mandatory public health surveillance since 1996 in Poland. Here, the incidence, temporal trends, and geographical distribution of LB and its manifestations in Poland are described for the period 2015-2019. Methods: This retrospective incidence study of LB and its manifestations in Poland was based on the data sent to the National Institute of Public Health (NIPH-NIH–NRI) by district sanitary-epidemiological stations using the electronic Epidemiological Records Registration System and data from the National Database on Hospitalization. LB and its manifestations were reported in two categories- probable and confirmed (through laboratory tests). Incidence rates were calculated using the population data from the Central Statistical Office of Poland. Results: In Poland, a total of 94, 715 cases of LB with an overall mean incidence of 49.3 cases per 100, 000 population were reported between 2015-2019. Cases increased from 2015 (11, 945) to 2016 (20, 857), and then remained stable through 2019. LB was more common among women (55.7%). The highest incidence rates occurred among >50-year-olds, with a peak in 65-69-year-olds. 48, 717 persons with LB were hospitalized in the 5-year period, with higher number of hospitalizations in age groups 55-69 years old. Erythema migrans and Lyme arthritis were the most common manifestations of LB with incidence rates of 36.2 and 15.8 per 100, 000 population, respectively. EM accounted for approximately 74% of all manifestations of LB. The highest number of cases were recorded in the 3 rd and 4 th quarters of the year (July – December). Incidence rates in the East and Northeastern regions (Podlaskie, Lubelskie, and Warmińsko-Mazurskie voivodeships) of the country were higher than the national average. These regions correspond to greater forest cover and/or agricultural areas. Time trend of LB cases and incidence in Poland, 2015-2019. Conclusion: LB is endemic in all regions of Poland, and many regions reported high incidence rates. LB is reported year-round in Poland. Thus, large variations in temporal and spatially granular incidence rates highlight the need for targeted prevention strategies, such as vaccines. Disclosures: Jozica Skufca, Epidemiologist, p95: Paid by Pfizer to perform the study Archana Nagarajan, Ph.D., P95: Paid by Pfizer to perform the study Andreas Pilz, PhD, Pfizer: Employee|Pfizer: Stocks/Bonds|Pfizer: Stocks/Bonds Andrew Vyse, Ph.D., Pfizer: Stocks/Bonds Elizabeth Begier, M.D., M.P.H., Pfizer: Employee|Pfizer: Stocks/Bonds Mendwas Dzingina, Ph.D., Pfizer: Stocks/Bonds Maxim Blum, Ph.D., P95: Paid by Pfizer to perform the study Margarita Riera, MD, MPH, P95: Paid by Pfizer to perform the study Bradford Gessner, MD, MPH, Pfizer: Stocks/Bonds James Stark, Ph.D., Pfizer: Stocks/Bonds.